BRET based dual-colour (visible/near-infrared) molecular imaging using a quantum dot/EGFP–luciferase conjugate. Issue 60 (29th October 2019) - Tsuboi, Setsuko; Jin, Takashi
Abstract : A bioluminescent dual-colour molecular-imaging probe was prepared to emit green and near-infrared luminescence from a conjugate between enhanced green fluorescent protein (EGFP), Renilla luciferase (RLuc) and CdSeTe/CdS quantum dot (QD). Abstract : Owing to its high sensitivity, bioluminescence imaging is an important tool for biosensing and bioimaging in life sciences. Compared to fluorescence imaging, bioluminescence imaging has a superior advantage that the background signals resulting from autofluorescence are almost zero. In addition, bioluminescence imaging can permit long-term observation of living cells because external excitation is not needed, leading to no photobleaching and photocytotoxicity. Although bioluminescence imaging has such superior properties over fluorescence imaging, observation wavelengths in bioluminescence imaging are mostly limited to the visible region. Here we present bioluminescence resonance energy transfer (BRET) based dual-colour (visible/near-infrared) molecular imaging using a quantum dot (QD) and luciferase protein conjugate. This bioluminescent probe is designed to emit green and near-infrared luminescence from enhanced green fluorescent protein (EGFP) and CdSeTe/CdS (core/shell) QDs, where EGFP– Renilla luciferase (RLuc) fused proteins are conjugated to the QDs. Since the EGFP–RLuc fused protein contains an immunoglobulin binding domain (GB1) of protein G, it is possible to prepare a variety of molecular imaging probes functionalized with antibodies (IgG). We show that the BRET-based QD probe can be used for highly sensitive dual-colour (visible/near-infrared) bioluminescence molecular imaging of membrane receptors in cancer cells.